(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article focuses on the performances performed since 2012 by the Anima Naturalis group in front of the Cathedral of Barcelona, ​​Spain. The performance consists of the presentation of 20 activists packed, tagged and smeared with artificial blood on trays similar to those used for selling meat in markets. When choosing this performance, our concern falls on the immanent scenic discourses that operate in the body and in the urban space, seeking new political, ethical and aesthetic dimensions. We also aim to understand how contemporary art desecrates the old image of the body idealized by art, affirming, in this case, the literality of the human body, questioning it and evoking the ambiguities that constitute our perception of it, at the level of its physicality, image and representation through processes of performative scenification.